Мышечная система клеща Varroa jacobsoni (Parasitiformes, Varroidae) — паразита медоносной пчелы. I. Мышцы гнатосомы - Акимов, И.А.; Ястребцов, А.В. (Вестник зоологии, 1983)
A detailed description is given to internal and external chelicerae muscles, pedipalp muscles, a complex of pharynx muscles, tritosternum muscle. Chelicera protractor muscles are not found. It is shown that specialization of the mite to feed on bee haemolymph induces no essential rearrangements in the muscular system of the gnathosoma.